AN APPROACH TO FUTURE TEACHER TRAINING PROCESS OF PRIMARY EDUCATION - Mireya Rubio-Moreno (Ra Ximhai, 2015)
This article presents partial results of a research about the processes lived in a more meaningful manner by the future teachers in primary education. The methodology is qualitative, a questionnaire and a semistructured interview were applied to twelve subjects, finding that a large part of them point to the experiences of observation and teaching practice as more significant to be suitable in their later professional practice. In contrast, few point to the weight of vocation, self taught and count with teachers engaged and capable for the consolidation of their professional skills. We conclude that the initial formative processes are diverse and complex with little impact on the theoretical and methodological domain of the teacher training students coming to graduating.